Get your coat: examining the development of independent dressing skills in young children with visual impairment, Down syndrome and typically developing children. Issue 3 (23rd February 2020) - Hayton, J.; Wall, K.; Dimitriou, D.
ABSTRACT: Dressing is a fundamental independent living skill (ILS). Vision is an integrative sense which affords learning via sighted observation. Visual impairment (VI) denies/restricts access to learning via sight. As a result, children with VI and conditions where VI may be a component (e.g. Down syndrome (DS)) require structured, systematic support to develop ILS. The current study used a repeated-measures-intervention approach to examine the development of the ILS of dressing (ILSD) with novel intervention materials in young children. Participants ( N = 27: age range 5;05–10;02 years) were drawn from three groups: VI ( n = 9; age range 5;05–10;02 years); DS ( n = 9; age range 5;05–10;00 years) and Typically Developing (TD) ( n = 9; age range 6;05–8;00 years). The effectiveness of the intervention materials was measured over a period of 10 weeks. Clear and systematic verbal instruction combined with motor activities was useful in supporting ILSD. The assessment of the longer-term effectiveness was carried out at 1 and 3 months post-intervention. This paper reported that the novel intervention materials supported the development of ILSD in all three groups. The findings could form a model for future work regarding the development of ILS in other skill areas and generalised to other developmental disorders.